KAJIAN PREFERENSI KONSUMEN TERHADAP BEBERAPA JENIS VARIETAS SORGUM MELALUI UJI ORGANOLEPTIK - Fifi Nur Janah; Umi Barokah (Yayasan Nusantara Hasana Berdikari, 2025)
High dependence on rice as the main food source has led to food insecurity in Indonesia. Sorghum (Sorghum bicolor L. Moench) has the potential as an alternative food source rich in nutrients (protein, fat, carbohydrates) to reduce dependence on rice. This research aims to determine the sensory characteristics of sorghum and reveal consumer preferences for various types of sorghum varieties. The research method used is descriptive involving organoleptic tests and consumer preference tests using hedonic rating and hedonic ranking methods. The results of this study revealed that various sorghum varieties showed significant differences in sensory characteristics, especially in the parameters of taste, aroma, texture and appearance. Consumer preferences for sorghum varieties show variations, with some varieties showing more desirable yields. This research concludes that sorghum has potential as an alternative staple food that needs to continue to be developed further, taking into account the sensory characteristics preferred by consumers.